2013
DOI: 10.1097/brs.0b013e318273a2ea
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adjacent Segment Degeneration After Spine Surgery

Abstract: Spine surgery is associated with significant risk of ASD. These figures may be useful in the estimation of the burden of the ASD after spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
130
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(140 citation statements)
references
References 91 publications
4
130
5
1
Order By: Relevance
“…Adjacent-level degeneration has been reported to occur after lumbar fusion surgery [14] . In a recent literature review, the rate of symptomatic ASD after decompression and stabilization procedures was approximated to 2%-3% per year [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Adjacent-level degeneration has been reported to occur after lumbar fusion surgery [14] . In a recent literature review, the rate of symptomatic ASD after decompression and stabilization procedures was approximated to 2%-3% per year [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The aim is to relieve clinical symptoms without considering the problem of fixed segment movement. Long-term follow-up reveals adjacent segment ROM increased to compensate for the lost ROM of the fixed segment, resulting in ASD [13][14][15][29][30][31][32][33]. Following improved knowledge of lumbar motion function, surgeons now consider how to treat lumbar degenerative disease while maintaining ROM, and dynamic stabilization has been developed and accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, decompression with fusion and internal fixation has been the mainstay of surgical approaches to the management of symptomatic LSS [3][4][5][6]. However, some authors reported that it may be related to other problems such as serious trauma, transfusion requirement, pseudarthrosis as well as higher morbidity and mortality for elderly patients [7][8][9][10], especially adjacent segment degeneration [11][12][13][14][15][16][17]. In order to overcome these deficiencies associated with fusion surgery, an interspinous process device-Coflex system (Paradigm Spine, LLC, New York) was developed as a possible alternative to spinal decompression with posterolateral fusion and instrumentation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Cependant, dans notre travail, les hyperfixations articulaires des DMA étaient dans la plupart des cas en rapport avec la symptomatologie du patient, établissant ainsi un lien entre l'augmentation réactionnelle du remodelage osseux et les douleurs. Sur le plan morphologique, différentes études dont une méta-analyse rapportent en cas d'arthrodèse l'apparition de signes radiologiques de DMA chez 29,3 à 49 % des patients sans corrélation avec le résultat fonctionnel puisque celle-ci n'est symptomatique que dans 7,4 % des cas [4,22]. Ainsi, il est possible que la scintigraphie avec TEMP présente une exactitude diagnostique supérieure au bilan radiologique conventionnel pour la dégénérescence articulaire chez les patients porteurs d'une arthrodèse.…”
Section: Les Dégénérescences Mécaniques Adjacentesunclassified